Thaumarchaeal ammonium oxidation and evidence for a nitrogen cycle in a subsurface radioactive thermal spring in the Austrian Central Alps - Gerbl, Friedrich W.; Weidler, Gerhard W.; Wanek, Wolfgang; Erhardt, Angelika; Stan-Lotter, Helga (Frontiers in Microbiology, 2014)
Previous studies had suggested the presence of ammonium oxidizing Thaumarchaeota as well as nitrite oxidizing Bacteria in the subsurface spring called Franz Josef Quelle (FJQ), a slightly radioactive thermal mineral spring with a temperature of 43.6 - 47oC near the alpine village of Bad Gastein, Austria. The microbiological consortium of the FJQ was investigated for its utilization of nitrogen compounds and the putative presence of a subsurface nitrogen cycle. Microcosm experiments made with samples from the spring water, containing planktonic microorganisms, or from biofilms, were used in this study. Three slightly different media, enriched with vitamins and trace elements, and two incubation temperatures (30 and 40oC, respectively) were employed. Under aerobic conditions, high rates of conversion of ammonium to nitrite, as well as nitrite to nitrate were measured. Under oxygen-limited conditions nitrate was converted to gaseous compounds. Stable isotope probing with 15NH4Cl or (15NH4)2SO4 as sole energy sources revealed incorporation of 15N into community DNA. Genomic DNA as well as RNA were extracted from all microcosms. The following genes or fragments of genes were successfully amplified, cloned and sequenced by standard PCR from DNA extracts: Ammonia monooxygenase subunit A (amoA), nitrite oxidoreductase subunits A and B (nxrA and nxrB), nitrate reductase (narG), nitrite reductase (nirS), nitric oxide reductases (cnorB and qnorB), nitrous oxide reductase (nosZ). Reverse transcription of extracted total RNA and real-time PCR suggested the expression of each of those genes. Nitrogen fixation (as probed with nifH and nifD) was not detected. However, a geological origin of NH4+ in the water of the FJQ cannot be excluded, considering the silicate, granite and gneiss containing environment. The data suggested the operation of a nitrogen cycle in the subsurface environment of the FJQ.